Hepcidin Attenuates Zinc Efflux in Caco-2 Cells. Issue 11 (21st September 2016) - Hennigar, Stephen R; McClung, James P
Abstract: Background: Hepcidin mediates the hypoferremia of inflammation by inhibiting iron transfer into circulation; however, a regulator for the hypozincemia observed in individuals with acute and chronic inflammatory and infectious diseases is not known. Objective: The objective of this study was to determine the effects of hepcidin on zinc transport in intestinal epithelial cells. Methods: Differentiated human intestinal Caco-2 cells were untreated or treated with 1 μM hepcidin for 3–24 h. Zinc transport was assessed in cells seeded on Transwell inserts. Media from the apical and basolateral chambers were collected, and zinc concentrations were determined using 67 Zn. Labile zinc pools were imaged and quantified in cells loaded with FluoZin-3-AM and expression of metallothionein and the zinc transporters zrt-/irt-like protein (ZIP)4 ( SLC39A4 ), ZIP5 ( SLC39A5 ), ZIP14 ( SLC39A14 ), and zinc transporter 1 (ZnT1) ( SLC30A1 ) was determined. Cells were transfected with SLC40A1 - or SLC30A1 -specific small interfering RNA to knock down ferroportin and ZnT1 protein, respectively. Cell surface proteins were isolated by cell surface biotinylation and lysosomal and proteasomal degradation was inhibited by treating cells with chloroquine or MG132, respectively. Results: Hepcidin attenuated zinc transport, as cells treated with hepcidin exported 26% less 67 Zn ( P < 0.05) into the basolateral chamber and retained 27% more cellular 67 Zn ( P < 0.05) than did control cells. Labile zinc decreased, and the mRNA abundance of metallothionein increased by ∼50% in hepcidin-treated cells compared with control cells ( P < 0.05). Hepcidin reduced ZnT1 protein by 75% ( P < 0.05) compared with control cells. Hepcidin-mediated reductions in zinc export remained in ferroportin knockdown cells compared with untreated controls ( P < 0.05), whereas knockdown of ZnT1 inhibited this effect ( P ≥ 0.05). Hepcidin significantly reduced biotinylated cell surface ZnT1 compared with control cells ( P < 0.05); chloroquine inhibited hepcidin-mediated degradation of ZnT1 ( P ≥ 0.05), whereas MG132 had no effect ( P < 0.05). Conclusions: Hepcidin reduces intestinal zinc export by post-translationally downregulating ZnT1 through a lysosomal-mediated degradation pathway, indicating that hepcidin may contribute to the hypozincemia of inflammation and infection.